Life satisfaction and healthy nutrition attitude in physically active and inactive university students - Ergüven, Ahmet Tarık; Teke, Mehmet Sait; Üstün, Ümit Doğan; Ekinci, Nurullah Emir (Progress in Nutrition, 2022)
Study Objectives: The present study aimed to analyze the differences in the perception of life satisfaction (LS) and healthy nutrition attitudes (HNA) of university students according to general practice physical activity results. Analyzing the effect of HNA on LS was another aim. Materials and Method: A cross-sectional questionnaire survey administered to Hatay Mustafa Kemal University students, and randomly chosen 498 university students participated in the study. The data was analyzed with SPSS 23.0. In the analyzes of the data One Way ANOVA and Simple Linear Regression were used. Results: 32.9% of the participants were found to be physically active and reporting significantly higher life satisfaction than physically inactive and moderately inactive students. Physically inactive students reported lower healthy nutrition attitude than moderately active and active students. Healthy nutrition attitude significantly predicts life satisfaction for all participants regardless of their physical activity index. Conclusion: To achieve substantive life satisfaction, healthy nutritional attitudes should be developed.